Вплив делеції гена β-катеніну на морфологію та фізіологію кардіоміоцитів за умов дії стимуляторів гіпертрофії - Пальчевська, О.Л.; Хазєєва, А.А.; Мачушинець, Н.В.; Рубан, Т.П.; Мацевич, Л.Л.; Півень, О.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. The investigation of β-catenin signaling function during cardiomyocyte hypertrophy development under the one
allele of β-catenin conditional cardiospecific knock-out condition was the aim of present work. Methods. The heart
of new-born trangenic and wild-type animals were used for the primary culture isolation. The physiological activity
was evaluated with MTT-test. The primary cardiomyocytes were H&E stained and morphological parameters were
measured. Results. The physiological activity elevation was detected for wild-type and haploinsufficient animals after
lithium chloride treatment comparing to control cells in MTT-test. The inhibition of physiological activity was detected
for all genotypes comparing to controls. The binucleated cells distribution was shown to differ between the control and
LiCl-treated cells. Also the frequency of binucleated cells tended to increase for mutants comparing to controls after
canonical Wnt stimulation with LiCl. Conclusions. The deletion of β-catenin leads to disruptions in cell morphology
and physiology in postnatal cardiovyocytes and attenuated cell hypertrophy development possibly due to canonical Wntsignaling inhibition.
Keywords: hypertrophic stimuli, β-catenin haploinsufficiency, β-catenin deletion, canonical Wnt-signaling.